Pertumbuhan Ekonomi Pulau Sumatera - Wahyudi, Heru; Silpayana, Silpayana (Jurnal Studi Pemerintahan dan Akuntabilitas, 2022)
Purpose: This research aims to analyze effect of Domestic Investment, Population and Labor Force on Economic Growth in the island of Sumatera. Research methodology: The analytical method used in this study is Panel Least Squares (PLS) analysis with the help of the eviews 9. program. The data used in this analyze is panel data with a cross-section combination of 10 provinces and time-series in the period 2015 to 2019. Result: The result of this study indicate that together domestic investment, population and labor force have a significant effect on economic growth. Partially, domestic investment has not significant effect on economic growth, population has a significant positive effect on economic growth and labor force has a significant positive effect on economic growth. Limitations: The sample of this study is the use of a less specific indicator of economic growth variables. Contribution: This research is helpful for further research. One of the guidelines in choosing which variabels to use and which one to use in the study should be understood in selecting indicator of economic.